The Effect of Profitability, Operating Cash Flow, and Market Value on Stock Return with Company Size as a Moderation: A Study of Companies Listed on the IDX 30 Index (Period 2021–2023) - Dzaironi, Muhammad; Permata , Lukita Tri; Pebriani , Reni Aziatul (Golden Ratio of Finance Management, 2026)
This research is motivated by the importance of investors' understanding of the factors influencing stock returns , particularly in the context of companies included in the DX30 index. The main issue raised is how profitability, operating cash flow, and market value influence stock returns , and whether company size can strengthen this relationship. This study aims to empirically test the effect of these three independent variables on stock returns , using company size as a moderating variable. The method used is a quantitative approach with multiple linear regression analysis and moderated regression analysis (MRA), using secondary data from 23 DX30 companies during the 2021–2023 period. The results of the study indicate that profitability and market value have a significant positive effect on stock returns , while operating cash flow has no significant effect. Company size does not moderate the relationship between profitability and operating cash flow on stock returns . Therefore, investors are advised to consider profitability and market value more carefully when making investment decisions, as company size does not always strengthen the company's performance signal on stock returns.